The Book of the Wiles of Women - Keller, John Esten (MLA translation series ;, 2019)
First rendered into Spanish from Arabic in 1253, this book became the inspiration for many great books of European literature. Keller's translation of this collection of Jewish and Islamic folklore will be of value to folklorists and students of Spanish and comparative literature, and will also interest anyone who likes lively tales.